Ամերկոմի եւ ՀԽՍՀ իշխանութիւնների փոխյարաբերութիւնները 1920 ականներին - Աւետիսեան, Սուրէն (տպ. Atlas)
In the first half of the 1920s, the activity of the American Committee for Relief in the Near East (ACRNE) had a relatively serious and positive impact on the internal life of Soviet Armenia. The support of the Soviet authorities was a serious factor in the effective and normal organization of those works, which were the basis for the formation of regulated relations with ACRNE. ACRNE’s work covered the domains of: the living and upbringing of children in orphanages, issues of emigrant support, and the formation and regulation of relations with the Soviet authorities. The formation of relations with the Soviet authorities was regulated by an appropriate agreement, which had a positive effect on the implementation of activities. Summarizing the activities of ACRNE in Soviet Armenia, it becomes quite clear that the latter had a positive impact on the improvement of the socio-economic situation.
Keywords: Միջազգային յարաբերութիւններ